Influenza H1N1pdm‐specific maternal antibodies offer limited protection against wild‐type virus replication and influence influenza vaccination in ferrets. Issue 2 (16th December 2013) - Suguitan, Amorsolo L.; Zengel, James R.; Jacobson, Scott; Gee, Stephanie; Cetz, Janet; Cha, Paulyn; Chen, Zhongying; Broome, Rosemary; Jin, Hong
<x xml:space="preserve">Abstract</x> Objective The objective was to study passively acquired influenza H1N1 pandemic (H1N1pdm) maternal antibody kinetics and its impact on subsequent influenza infection and vaccination in ferrets during an outbreak of the H1N1pdm. Design and main outcome measures Infectivity of the H1N1pdm in the respiratory tract of ferrets was compared with the previous seasonal A/South Dakota/6/2007 (SD07, H1N1). Influenza‐specific antibodies were quantitated and antibody‐mediated protection against the homologous and heterologous H1N1 virus challenge infection was determined. Results H1N1pdm virus was approximately 10 times more infectious than SD07 in ferrets, replicated to higher viral titers in the upper respiratory tract and shed for a longer duration. Influenza‐specific antibodies after natural infection persisted much longer in the circulation than passively acquired maternal antibodies. The protection conferred by the maternal antibodies was limited to the homologous virus strain and was ineffective against SD07 and H3N2 virus. Serum antibodies from maternal transmission or passive transfer interfered with homologous vaccine strain‐mediated antibody responses in the ferret. A booster immunization was required to elicit a high level of antibody. Conclusions The findings support the rationale for a prime and boost immunization strategy in young children in whom maternal antibodies are present.